أثر استخدام أدوات الذكاء الاصطناعي في تحسين العملية المحاسبية - بوبكر، ياسين; قرفي ،يمينة (جامعة الوادي University of Eloued, 2025)
تهدف هذه الورقة البحثية الى دراسة الذكاء الاصطناعي ومدى أثره في تحسين العملية المحاسبية، ولذلك تناول الجزء الأول من هذه الورثة مختر التأصيل النظري للذكاء الاصطناعي وعلاقته بمهنة المحاسبة، كما تناول الجزء الثاني دراسة ميدانية تمثلت في توزيع الاستمارات وتحليل نتائجها احصائيا، لذلك تم استخدام المنهج الوصفي والتحليل الملائم لهذا النوع من الدراسات. ولقد توصلت هذه الدراسة إلى جملة من النتائج أهمها أن استخدام الذكاء الاصطناعي يحسن من العملية المحاسبية من عدة جوانب منها انه يخفض من معدلات الأخطاء البشرية و يحسين من دقة البيانات وسلامتها، وكذلك يساهم في تحقيق الكفاءة وتوفير الوقت دون ان ننسى انه يساهم في إعداد التقارير في الوقت الحقيقي كما انه يتميز بقابليته على التوسع والقدرة على التكيف. This article aims to study artificial intelligence and its impact on improving the accounting process. Therefore, the first part of the paper addresses the theoretical foundation of artificial intelligence and its relationship with the accounting profession. The second part focuses on a field study, which involved distributing questionnaires and statistically analyzing the results. Accordingly, the descriptive and analytical methodology was adopted, as it is suitable for this type of study. The study reached a set of conclusions, the most important of which is that the use of artificial intelligence enhances the accounting process in various aspects. It reduces human error rates, improves the accuracy and integrity of data, contributes to achieving efficiency and saving time, and enables the preparation of real-time reports. Moreover, it is characterized by scalability and adaptability.
The Impact of Using Artificial Intelligence Tools on Improving the Accounting Process A Field Study on a Sample of Accounting Professors and Accountants
مقال
Keywords: الذكاء الاصطناعي; المحاسبة; العملية المحاسبية; Artificial Intelligence; Accounting; Accounting Process